Globalization: an approach from biological evolution and self-organizing complex systems (2007)
The past two decades have witnessed a dramatic increase of the literature devoting attention to globalization. However, the high complexity of this phenomenon seems to defy its precise and essential definition. In characterizing globalization, we give support to the perspective of non-equilibrium self-organization instead of that related with the application of Darwinian biological analogies of natural selection to socio-economic evolution. A thermodynamic approach to the emergence of social systems is presented, in addition to the notion of transition from biological to social evolution. This paper aims to address the phenomenon of globalization in terms of a state, a structure and a process, within the framework of the complex and selforganizing systems.